TRANSLATION TECHNIQUES OF LITTLE PRINCE’S INTERROGATIVE UTTERANCES IN THE LITTLE PRINCE NOVEL INTO INDONESIAN PANGERAN CILIK - Armyla Armyla; Singgih Daru Kuncara; Chris Asanti (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTThis research analyzed translation techniques used in the translation of interrogative utterances by Little Prince’s character in the English novel The Little Prince into Indonesian Pangeran Cilik by Antoine De Saint-Exupery. The researcher used the theory of translation techniques by Molina and Albir (2002). This research was categorized as qualitative research. The result of the research showed there were 12 techniques used in the data. They were, namely, adaptation, borrowing, compensation, description, discursive creative, established equivalent, linguistic amplification, linguistic compression, modulation, reduction, and transposition. The total data were 97 interrogative utterances by Little Prince’s character. The total data of each techniques were as follows: (1) adaptation occurred 3 times, (2) amplification occurred 3 times, (3) borrowing occurred 1 time, (4) compensation occurred 3 times, (5) Description occurred 2 times, (6) discursive creation occurred 4 times, (7) established equivalent occurred 6 times, (8) literal translation occurred 38 times, (9) modulation occurred 6 times, (10) reduction occurred 23 times, (11) transposition occurred 8 times. The researcher found the dominant technique used by the translator was literal translation with total of 38 findings.Key words: Translation, Translation Technique, Interrogative Utterances, The Little Prince, Pangeran Cilik ABSTRAKPenelitian ini menganalisis teknik penerjemahan yang digunakan dalam penerjemahan ujaran interogatif tokoh Pangeran Kecil dalam novel Bahasa Inggris The Little Prince ke Bahasa Indonesia Pangeran Cilik karya Antoine De Saint-Exupery. Peneliti menggunakan teori teknik penerjemahan oleh Molina dan Albir (2002). Penelitian ini termasuk penelitian kualitatif. Hasil penelitian menunjukkan ada 12 teknik yang digunakan dalam data. yaitu, adaptasi, peminjaman, kompensasi, deskripsi, kreasi diskursif, bentuk padanan, amplifikasi linguistik, kompresi linguistik, modulasi, reduksi, dan transposisi. Total data adalah 97 ujaran interogatif dari karakter Pangeran Kecil. Total data dari masing-masing teknik adalah sebagai berikut: (1) adaptasi ditemukan 3 kali,(2) amplifikasi (3) peminjaman ditemukan 1 kali, (3) kompensasi ditemukan 3 kali, (4) deskripsi ditemukan 2 kali, (5) kreasi diskursif ditemukan 4 kali , (6) bentuk padanan ditemukan 6 kali, (9) terjemahan literal ditemukan 38 kali, (10) modulasi muncul 6 kali, (11) reduksi muncul 23 kali, (12) transposisi ditemukan 8 kali. Peneliti menemukan teknik yang dominan digunakan oleh penerjemah adalah terjemahan literal dengan total 38 temuan.Kata kunci: Penerjemahan, Teknik Penerjemahan, Ujaran Interogatif, The Little Prince, Pangeran Cilik